Diagnóstico de la valoración psiquiátrica, conforme lo señala el código orgánico integral penal, para acogerse a la inimputabilidad del procesado - Cuesta Cirino, Franklin Santiago (2018)
In the present investigation, the present topic was developed: DIAGNOSIS OF PSYCHIATRIC ASSESSMENT, AS INDICATED BY THE COMPREHENSIVE ORGANIC CODE, TO ACCOMPANY THE IMPARTIALITY OF THE INDICTED. Developing research under the general objective: Establish the importance of assessing psychiatrically the active subject of a crime during pre-trial investigation, during the process and in the execution of the sentence, which allows to define the degree of mental disorder suffered, at the rate of to determine its imputability, with the purpose of guaranteeing the rights of people who really suffer from a mental disorder and that they have committed an infraction. In order to achieve the objectives set out in this research, the study methods were used: qualitative, quantitative, analytical, explorative. Using data collection techniques such as the survey and the interview, which were addressed to lawyers registered in the School of the city of Guayaquil, who exercise their profession as judges, prosecutors, public defenders, expert experts, in order to know the criteria what they have about the problem…….